Environmental Information Required by Individuals with Visual Impairments Who Use Orientation and Mobility Aids to Navigate Campuses. (July 2020) - Papadopoulos, Konstantinos; Charitakis, Konstantinos; Koustriava, Eleni; Kouroupetroglou, Georgios; Stiefelhagen, Rainer; Stylianidis, Efstratios; Gumus, Suad Sakalli
Introduction: This study investigated the user requirements of individuals with visual impairments regarding the information to be included in orientation and mobility (O&M) aids in order for optimally useful audio-tactile maps of campuses to be developed. In addition, this study aimed at investigating the importance (usefulness) that individuals with visual impairments attribute to environmental information of campuses. Methods: The researchers listed 213 pieces of environmental information concerning campuses and address them in survey by conducting a respective questionnaire. Participants were asked to evaluate the information, regarding the importance or usefulness of the information in regard to safety, location of services, and orientation and wayfinding during movement. Through convenience sampling 115 adults (aged from 18 to 64 years) with visual impairments from four countries (Greece, Cyprus, Turkey, and Germany) took part in the research. Results: Pieces of environmental information, sorted in descending order starting with the most useful ones, have been listed. A repeated measures analysis of variance yielded a significant main effect for the type of information (safety, location of services, and wayfinding and orientation): F (2, 228) = 70.868, p < .001. Discussion: This study resulted in the specification of the most significant or useful information that should be included in O&M aids of campuses for individuals with visual impairments. Implications for practitioners: The results of this study will hold the interest of developers of O&M aids, O&M practitioners, rehabilitation teachers, and instructors who design and construct O&M aids. Moreover, the context for appropriately designed tactile or audio-tactile maps for campuses is provided, and campuses around the world could rely on this study for the creation of a valuable accessibility aid.